Influence of mud intercalation on the stability of seepage flow in tailings dams - Li, Hongru; Yang, Min; Dang, Tong (Frontiers in Earth Science, 2023)
Layers with low permeability is an important factor affecting the stability of tailings dam. In order to analyze the influence of the weak permeability interlayer on the seepage stability of the dam body, this paper establish a numerical analysis model of the tailings dam with the weak permeability interlayer. The seepage stability of dam slope is calculated and analyzed for the location, thickness, number and intervals of mud intercalation on the seepage stability of dam slope. Weakly permeable interlayers at different positions form different saturation lines in the dam. When the weak permeability interlayer is located in the middle of the dam, the height of the saturation line is the highest, and the corresponding stability safety factor is the smallest. When the weak permeability interlayer moves up or down, the buried depth of the saturation line increases and the safety factor increases. However, when the weak permeability interlayer is located above the drainage prism, the overall slip along the weak permeability interlayer is incidental with the increase of dam height. When the thickness of the weak permeability interlayer changes, the safety factor of the dam has positively high significance related to the leakage. When the position of the weak permeability interlayer changes, the safety factor of the dam no obvious correlation with the leakage. With the increase of the thickness and number of weak permeability interlayer and the decrease of the intervals of mud intercalation, the height of the saturation line gradually increases, and the safety factor of the dam body gradually decreases. Through the position of the sliding surface, it is found that the sliding surface eventually destabilizes through the lowest weak permeability interlayer.